Dexamethasone and potassium canrenoate alleviate hyperalgesia by competitively regulating IL‐6/JAK2/STAT3 signaling pathway during inflammatory pain in vivo and in vitro. Issue 11 (26th October 2022) - Liu, Jie; Xie, Xiaolan; Qin, Kai; Xu, Le; Peng, Juxiang; Li, Xiangyu; Li, Xiongjuan; Liu, Zhiheng
Abstract: Background: Dexamethasone (Dexa) and potassium canrenoate (Cane) modulate nociceptive behavior via glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) by two mechanisms (genomic and nongenomic pathways). This study was designed to investigate the Dexa‐ or Cane‐mediated nongenomic and genomic effects on mechanical nociception and inflammation‐induced changes in interleukin‐6 (IL‐6) mediated signaling pathway in rats. Methods: Freund's complete adjuvant (FCA) was used to trigger an inflammation of the right hind paw in male Sprague–Dawley rats. First, the mechanical nociceptive behavioral changes were examined following intraplantar administration of GR agonist Dexa and/or MR antagonist Cane in vivo. Subsequently, the protein levels of IL‐6, IL‐6Rα, JAK2, pJAK2, STAT3, pSTAT3 Ser727, migration inhibitory factor, and cyclooxygenase‐2 were assessed by Western blot following intraplantar injection of Dexa or Cane or the combination. Moreover, the molecular docking studies determined the interaction between Dexa, Cane, and IL‐6. The competition binding assay was carried out using enzyme‐linked immunosorbent assays (ELISA). Results: Administration of Dexa and Cane dose‐dependently attenuated FCA‐induced inflammatory pain. The sub‐additive effect of Dexa/Cane combination was elucidated by isobologram analysis, accompanied by decrease in the spinal levels of IL‐6, pJAK2, and pSTAT3 Ser727 . The molecular docking study demonstrated that both Dexa and Cane displayed a firm interaction with THR 138 binding site of IL‐6 via a strong hydrogen bond. ELISA revealed that Dexa has a higher affinity to IL‐6 than Cane. Conclusions: There was no additive or negative effect of Dexa and Cane, and they modulate the IL‐6/JAK2/STAT3 signaling pathway through competitive binding with IL‐6 and relieves hypersensitivity during inflammatory pain. Abstract : FCA‐induced peripheral inflammatory pain cause central sensitization leading to the release of proinflammatory cytokine IL‐6, local intraplantar injection of Dexamethasone (Dexa) or Potassium canrenoate (Cane) competitively engage in IL‐6‐mediated IL‐6R/JAK2/STAT3 signaling pathway, in which Dexa was dominant in binding to IL‐6, thus regulating inflammatory pain. FCA, Freund's complete adjuvant; IL‐6, Interleukin 6; IL‐6R, Interleukin 6 receptor; JAK2, Janus kinase 2; STAT3, Signal transducer and activator of transcription 3;